"Enraizamento de esperança" : as bases teóricas do movimento de Educação de Base em Goiás - RODRIGUES, Maria Emília de Castro (2008)
Our Subject of study in the line research the Education, Work and Social Moviments of the Education Doctorate, the Movement of Basic Education in Goiás (MEB-Goiás), in the 1960s, carried out the process of adult education in rural areas, through the radio. It is a case built through the review of the literature related to the theme; by the analysis of documents (books, newspapers, texts, theses and dissertations, literature, poetry, songs, letters, interviews etc.), that recover stories of life and actions of those who built the MEB-Goiás, pursuing to capture theoretical and philosophicalpolitical benchmarks which influenced and argued its political-educational practice. The datas were analyzed based on readings of works from authors like Amado, Bosi, Brandão, Chardin, Fávero, Freire, Kadt, Lima e Arantes, Mounier, Peixoto Filho, Pessoa, Queiroz, Thompson, Vaz, and others. The analysis of the MEB-Goiás, in 1961 the 1966, indicated that the political and educational practice historically situated and therefore with the peasants, was a result of a possible construction, because of the confluence of a number of factors, like: the historic moment; the histories of life, commitment and militancy of Team Central and monitors the movement, supporting popular adults literacy/education articulated to the aims and needs of workers from rural areas; the dialogue with the theoretical reference from MEB-Nacional, from national and international authors in Church, social movements and popular education; the option, from the end of 1962, for a critical and transforming education.